Criminal background check laws and labor market inequality in the United States - McElhattan, David (Criminology & public policy, 2024)
Research summary A growing literature documents the effect of criminal justice contact on inequalities in the labor market. While ample evidence indicates that a criminal record itself imposes considerable disadvantage, the formal legal mechanisms that may contribute to criminal record-based exclusion have received less empirical attention. The present study examines how one such mechanism—legal requirements for employers and license boards to perform criminal background checks—shapes labor market outcomes among formerly incarcerated people. The study draws from novel longitudinal data on the extensiveness of background check requirements at the state level, as well as individual-level data on incarceration, wages, and unemployment from the Panel Study of Income Dynamics. Results show that while the extensiveness of state-level background check requirements does not significantly affect the likelihood of unemployment, formerly incarcerated people residing in states where background check requirements are extensive are estimated to earn significantly lower wages than their counterparts in states with few screening mandates. Policy implications Criminal background check requirements stand as significant policy barriers that diminish the earning potential of formerly incarcerated people. Policy makers seeking to mitigate the collateral consequences of criminal convictions should narrow the scope of these laws to target specific, highly sensitive occupations, as opposed to broader workplace contexts. Reforms should also address persistent data quality issues in state criminal history record systems and shift the burdens imposed by incomplete or erroneous rap sheets. To minimize adverse self-selection, background check procedures should clarify for applicants the role that a criminal history record may play in clearance decisions. Finally, future research should assess the marginal benefit of criminal background checks compared with other methods of screening prospective hires and licensees.